Antitumor effects of synthetic 6,7-annulated-4-substituted indole compounds in L1210 leukemic cells in vitro - Perchellet, Jean-Pierre H.; Waters, Andrew M.; Perchellet, Elisabeth M.; Thornton, Paul D.; Brown, Neil; Hill, David; Neuenswander, Ben; Lushington, Gerald H.; Santini, Conrad; Chandrasoma, Nalin; Buszek, Keith R. (My University, 2013)
Background: Because annulated indoles have almost no representation in the PubChem or MLSMR databases, an unprecedented class of an indole-based library was constructed, using the indole aryne methodology, and screened for antitumor activity. Sixty-six novel 6,7-annulated-4-substituted indole compounds were synthesized, using a strategic combination of 6,7-indolyne cycloaddition and cross-coupling reactions under both Suzuki-Miyaura and Buchwald-Hartwig conditions, and tested for their effectiveness against murine L1210 tumor cell proliferation in vitro. Materials and Methods: Various markers of tumor cell metabolism, DNA degradation, mitotic disruption, cytokinesis and apoptosis were assayed in vitro to evaluate drug cytotoxicity. Results: Most compounds inhibited the metabolic activity of leukemic cells in a time- and concentration-dependent manner but only 9 of them were sufficiently potent to inhibit L1210 tumor cell proliferation by 50% in the low-μM range after 2 (IC[subscript 50]: 4.5-20.4 μM) and 4 days (0.5-4.0 μM) in culture. However, the antiproliferative compounds that were the most effective at day 4 were not necessarily the most potent at day 2, suggesting different speeds of action. A 3-h treatment with antiproliferative annulated indole was sufficient to inhibit, in a concentration-dependent manner, the rate of DNA synthesis measured in L1210 cells over a 0.5-h period of pulse-labeling with [superscript 3]H-thymidine. Four of the antiproliferative compounds had weak DNA-binding activities but one compound reduced the fluorescence of the ethidium bromide-DNA complex by up to 53%, suggesting that some annulated indoles might directly interact with double-stranded DNA to disrupt its integrity and prevent the dye from intercalating into DNA base pairs. However, all 9 antiproliferative compounds induced DNA cleavage at 24 h in L1210 cells, containing [superscript 3]H-thymidine-prelabeled DNA, suggesting that these antitumor annulated indoles might trigger an apoptotic pathway of DNA fragmentation. Indeed the antiproliferative annulated indoles caused a time-dependent increase of caspase-3 activity with a peak at 6 h. Interestingly, the compounds with the most potent antiproliferative IC50 values at day 2 were consistently the most effective at inhibiting DNA synthesis at 3 h and inducing DNA fragmentation at 24 h. After 24-48 h, antiproliferative concentrations of annulated indoles increased the mitotic index of L1210 cells and stimulated the formation of many bi-nucleated cells, multi-nucleated cells, apoptotic cells and micronuclei, suggesting that these antitumor compounds might enhance mitotic abnormality, induce chromosomal damage or missegregation, and block cytokinesis to induce apoptosis. Conclusion: Although annulated indoles may have interesting bioactivity, novel derivatives with different substitutions must be synthesized to elucidate structure-activity relationships, identify more potent antitumor lead compounds, and investigate their molecular targets and mechanisms of action.
Keywords: Annulated indoles; Tumor cell proliferation; DNA synthesis; Interaction and fragmentation; Cells with mitotic figures; Several nuclei and micronuclei; Cytokinesis; Apoptosis